Variation of the nuclear ribosomal region in Crataegus L. from central and southern Mexico. - Nuñez-Colín, Carlos Alberto (2011)
This study was conducted at the Universidad Autónoma de Chapingo and concluded in October 2008, to determine the genetic relationships among species of Crataegus fromcentral and southern Mexico. The variation in the sequences of the nuclear ribosomal region was low in all accessions of germplasm of Mexican Crataegus, and the phylogramonly showed separation of the species used as positive controls, but did not show a clear separation of groups of species. However, all accessions had the same pattern of nucleotide substitution and very low values of the distanceof nucleotide composition; thus, Mexican Crataegus species have high genetic relationship among them, but there is alack of evidence to conclude that they are variants of the same taxonomic species. C. nelsoni and C. stipulosa could be a source of genes for C. mexicana because both species,from Chiapas, have the closest relationship with this species,which has the best agronomic characteristics.